Impact of High-Heeled Footwear on the health of the young female students of selected colleges of Mangalore, India - Vinutha Dsouza; Ruveena Menezes; Sheetal Theresa Dsouza (Occupational Health and Safety Society of Nepal, 2024)
Introduction: High-heeled shoes are a leading cause of foot problems and chronic lower limbs, as well as discomfort, fatigue, and an increased risk of injury. The research aimed to analyze the influence of wearing high-heeled shoes on the foot health of young females. The study emphasizes the need to create awareness among females about the detrimental impacts of utilizing heeled footwear over the long term on discomfort, BMI, and functional capacity. A slight change in footwear choices could significantly reduce discomfort and disability experiences. Methods: Purposive sampling was used to select 50 young female students studying in Mangalore's undergraduate college for the cross-sectional study. A pre-designed and pre-tested structured Google Form questionnaire was used to examine the socio-demographic characteristics and outcome measures, including the location of pain, the intensity of the pain, and functional ability. Data was collected in the second half of 2020. Descriptive and inferential statistics were used to analyze the data. Results: According to the survey, 46% of young female students exhibited poor functional activities while wearing high heels. It was found that 12% of students had pain in their toes all of the time, 8% had pain in the arch of their foot, and 25% had discomfort in their lower back occasionally. About two-thirds (64%) felt averagely manageable discomfort. Conclusion: The study found that wearing heeled shoes has a significant influence on women's musculoskeletal systems. Young females will be better able to resist pain from the deforming effects of footwear if they condition their feet properly and choose the appropriate footwear.